HUBUNGAN ANTARA STRUKTUR MODAL DAN KINERJA PERBANKAN SYARIAH DI INDONESIA - Ryan Bayukresna; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
Capital Structure is an important component for finance company such as bank corporation. Because capital structure composition have an effect on company performance. This study aim to examine relationship between capital structure and performance islamic bank in Indonesia. Capital Structure was measured using capital ratio, short them funding, productive asset, overhead, asset size and risk. While performance of islamic bank variable measured using Return On Equity ratio.This study using secondary data of annual report and financial report that comes from entire population of listed islamic bank on Indonesia. Which has completed annual and financial report during 2010 until 2013. Sample Consist of 36 company listed during time observation. Method used for determine sample is purposive sampling method. Moreover, analytical method used is ordinary least square regression with SPSS.The result of this study showed that capital ratio, short term funding, overhead and size of asset have significant relationship with performance of islamic banks. Meanwhile, productive asset and risk doesn’t have significant relationship with performance of islamic banks.